Genotoxic effects among petrol station workers. - Al-Faisal, Abdul-Hussain M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Benzene has been internationally recognized as a potent toxin, particularly for its effects on the blood forming system of the bone marrow and its association to a large number of haematological disorders. Aims: This study aimed to assess the cytogenetic damages related to occupational exposure to benzene by calculating the mitotic index ( MI) , nuclear division cytotoxicity index ( NDCI), binucleated cells ratio and chromosomal aberrations. Obgectives: Peripheral blood samples were collected from 30 benzene exposed workers and 10 from unexposed- controls- persons. 20 out of the exposed workers were occupationally exposed to benzene from 2 to more than 4 years. The rest of workers were exposed to benzene from one month to one year. Results: The mean MI in the benzene exposed workers ( 5.72 ± 0.62 ) M’as found significantly higher than in controls ( 4.03 ±0.37 ). The highest MI mean M’as calculated in the exposure group 4 to above vears.The NDCI of the exposure workers ( 3.38 ±0.54 )was also significantly higher than in control ( 2.04 ± 0.76 ).Lower NDCI mean was calculated in the 4 to above years exposure. Conclusions: Chromosomal aberrations were observed in the exposed group. Polyploidy , anuploidy ( 5 monosomy and 9 trisomy ) and structural aberration ( del 8q ) were detected in the exposed groups 0-3 years. MN frequencies were significantly increased in relation with length of employment. According to the KIN results and the chromosomal aberrations detected in the exposed groups, it could be possible that a correlation found between the elevated values of the KIN and the detected chromosomal aberrations. Keywords: Benzene, Chromosomal aberrations, AIN